Nutritional Knowledge and Beliefs between Fitness Room Users and Swimmers: 健身室使用者及游泳人仕的營養知識及信念的研究 - MA, Regine (Asian Journal of Physical Education & Recreation, 2000)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. The main purposes of the present study were to investigate the situation of nutritional knowledge and beliefs of 73 adults fitness room users (FRU) and 58 adult swimmers (SWR) and the ranged in age from 18 〜 65 years. Subjects selected from 5 different health clubs and swimming pools. It included community, commercial or corporate center and located at Hong Kong Island or Kowloon. A total 131 of adults completed the questionnaires, which included (a) background information, (b) multiple choice nutrition knowledge questions and (c) true-or-false nutrition belief statements. 2X2 ANOVA and Pearson correlation were utilized to analyze the different in between the nutritional knowledge and beliefs in exercise groups and gender. Results show that the FRU and SWR scores of nutritional knowledge and beliefs were low and no significant differences were found between exercise groups and gender. Only significant difference in relationship in nutrition knowledge and belief on swimmer group was observed. 此研究目的是探討成人健身室使用者(N=73)及游泳人仕(N=58)們對營養知識及飲食信念的情況。從五間不同的健體會所及游泳池中邀請受訪者完成一份問卷調查。受訪對象的年齡介乎18至65歲。此五間會所位於香港及九龍等地，會所形式包括：社區，私人及公司所屬之會所等。共131人完成此問卷調查，而問卷分為三部份；甲部：個人資料，乙部：營養知識及丙部：飲食信念。營養知識以多項選擇的提問方式，而飲食信念以是與否作判斷問題的真確性。用2x2ANOVA 及Pearson的相關系數分析兩運動組別及性別對營養知識及飲食信念之差別。結果指出健身室使用者及游泳人仕們對營養知識及飲食信念的分數也低。唯游泳人仕對營養知及飲食信念有相互關係。